Pediatric Thoracic Empyema-Outcomes of Intrapleural Thrombolytics: Ten Years of Experience - Aram Baram MD, MRCSEd, FACS, AFSCTS; Fitoon Yaldo MBChM (SAGE Publishing, 2020)
Introduction . Pediatric thoracic empyema is a special entity with increasing frequency. Consensus regarding the best management strategy is still evolving. We describe our single-center 10-year experience adopting intrapleural thrombolytics using tissue plasminogen activator as first-line treatment following failure of simple thoracostomy drainage techniques. Methods . Observational prospective study included all children from 1 day to 18 years admitted for parapneumonic effusion and treated with intrapleural thrombolytics. Results . From January 2008 to December 2018, 95 patients were treated by intrapleural thrombolytics for different stages of empyema thoracis. Number of thrombolytic doses required is 2.1 (range = 1-3), and mean amount of drainage is 1050 mL (range = 400-2500 mL). Mean total days of hospitalization is 7.3 days. Complete re-expansion was the primary outcome in 94 patients (98.9%). Conclusion . Intrapleural thrombolytics in complicated pediatric thoracic empyema results in excellent outcome and should be encouraged particularly in limited resource countries.